Rectal stenosis after immunotherapy in a mismatch repair deficient rectal cancer. Case report and review of literature - Marcel Büttner; Ulrike Schempf; Robert Bachmann; Rüdiger Hoffmann; Christopher Schroeder; Sven Mattern; Stephan Singer; Marc Steinle; Maximilian Niyazi; Michael Bitzer; Cihan Gani (Clinical and Translational Radiation Oncology)
We report the case of a 57-year-old male patient who presented with a circumferential cT3 cN1 rectal adenocarcinoma in the mid rectum. The tumor was found to be mismatch repair deficient/microsatellite instable (dMMR/MSI). Instead of multimodality treatment with chemoradiotherapy immunotherapy with Dostarlimab was initiated. Treatment was well-tolerated in general and endoscopy and MRI showed early signs of treatment response. Despite this, the patient developed intestinal obstruction due to scarring that required repeat balloon dilations. In contrast to other oncological treatments, obstructions may worsen during immunotherapy in dMMR rectal cancers. This information has to be considered when patients are consulted regarding the optimal treatment after disease.